The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5604/12314005.1165447
|View full text |Cite
|
Sign up to set email alerts
|

A Co-Generation Power Set With a Combustion Engine Fuelled by Wood Waste Gas

Abstract: This paper presents a concept and a technical analysis of a co-generation power set with a combustion engine powered by syngas produced in the process of wood waste gasification. The set is composed of a wood waste gas generator fitted with a filter system, a combustion engine, a current generator and heat exchangers. The foundations of the gasification process are described together with the most common solutions used worldwide. Moreover, the methods of adapting spark-ignition and compression-ignition engines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…They concluded that in order to reach high thermal efficiency and stable engine operation when operating with low-calorific-value fuels that contain mixtures of inert gases, it is desirable to use a stoichiometric premixture and adopt at high load conditions. A combustion engine was modified by Taler et al 78 to be powered by syngas produced in the wood waste gasification process.…”
Section: Cogeneration Technologiesmentioning
confidence: 99%
“…They concluded that in order to reach high thermal efficiency and stable engine operation when operating with low-calorific-value fuels that contain mixtures of inert gases, it is desirable to use a stoichiometric premixture and adopt at high load conditions. A combustion engine was modified by Taler et al 78 to be powered by syngas produced in the wood waste gasification process.…”
Section: Cogeneration Technologiesmentioning
confidence: 99%
“…The process is carried out in special devices called "gas generators" and it has many stages [1]. The gasification consists in thermal transformation of fuel in solid form (wood) into the gaseous fuel (wood gas) [2]. The gas consists of the combination of such flammable substances as: hydrogen, carbon oxide, methane and non-flammable -carbon dioxide, nitrogen, water vapour.…”
Section: Introductionmentioning
confidence: 99%